A protecção do consumidor nos contratos à distância face ao ordenamento jurídico angolano - Francisco, José Mateus (2017)
The objective of this research work is to carry out a theoretical study about the legal consumer protection in the Angolan reality, especially in distance contracts. Firstly, we did a legal analysis of the consumer rights in general. Secondly, the analysis focus in distance contracts (Commercial Activities Act, Civil CodeLaw, General Contract Terms Act, Consumer Protection Act).